A further HLA‐A*23 family allele – HLA‐A*23:68. (13th November 2015) - Street, J.; Lemin, A. J.; Darke, C.
Abstract : HLA‐A*23:68 differs from A*23:01:01 by one base (518C > A) in exon 3 resulting in an amino acid substitution of A149E.